An analysis of the effect of carbon emission, GDP and international crude oil prices based on synthesis integration model. Issue 4 (6th September 2018) - Zou, Xiaohua
Abstract : Purpose: This paper aims to analyze the impact of the relations between the US oil prices, carbon emissions and GDP through the analysis of data between 1987 and 2017. Design/methodology/approach: ARIMA, VAR and VEC models are used to establish synthesis integration model. Furthermore, the stability test, cointegration test and Granger causality test of the model were carried out. Findings: The results indicate that, in both short and long term, change in oil prices is the reason for change in carbon emissions, while GDP is not the reason for the growth of carbon emissions. Originality/value: Increase of oil prices would have a negative impact on carbon emissions, and GDP growth does not lead to an increase in carbon emissions.